Perbandingan Kualitas Citra Hasil Radiografi Thorax Proyeksi PA Menggunakan Grid dan Tidak Menggunakan Grid - Herlinda Mahdania Harun; Iffa Safira Luawo (Lontara Journal of Health Science and Technology, 2024)
The grid is an inspection tool that is used to absorb unidirectional scattered radiation originating from exposed objects. The routine projection for Thorax examinations is the Postero Anterior (PA) projection. This research was conducted to compare the results of PA projection Thorax radiographs using a grid and not using a grid. The type of research carried out was quantitative research with a comparative approach. The samples taken in this research were 2 samples with PA Thorax examination. Data collection was obtained from the densitomer tool, observation, and literature study. Based on research that has been carried out, the PA projection Thorax examination using a grid produces a better image compared to images that do not use a grid. Keyword : Radiographic Image Quality, Thorax, Grid